Negative effects of the SARS-CoV-2 pandemic: The interlinking of maternal attachment representation, coping strategies, parental behavior, and the child's mental health - Gulde, Manuela; Köhler-Dauner, Franziska; Mayer, Inka; Ziegenhain, Ute; Fegert, Jörg M.; Buchheim, Anna (Frontiers in Pediatrics, 2022)
For more than two years, young families have been confronted with a large number of restrictions and following burdens as a result of the SARS-CoV-2 pandemic. In fact, it became evident, that the current circumstances are particularly stressful for child's mental health. With regard to the child's mental health in times of a pandemic, additional factors within the family, such as maternal attachment representations as well as coping strategies and parental behavior, may play an important role. This study aims to investigate the interplay of maternal attachment representation, coping strategies, parental behavior and child's mental health during the SARS-CoV-2 pandemic. In this longitudinal study, previously collected data regarding maternal attachment representation and newly attained data from the SARS-CoV-2-pandemic-assesment (lack of coping strategies, children's mental health and parental behavior) were combined and analyzed. The data were collected in an online survey since beginning of the pandemic, including N = 73 mothers. A path model was calculated in form of multiple linear regression. A path model could be confirmed, which indicates that insecure maternal attachment representation predicts lack of coping strategies during the pandemic [b = 5.55, 95%-CI = (4.51; 6.55), p =<sans-serif> 0</sans-serif>.001]. Furthermore, lack of coping strategies predicts harmful parental behavior during the pandemic [b = −0.77, 95%-CI = (−1.27; −0.21), p =<sans-serif> 0</sans-serif>.007], which in turn predicts children's mental health problems, namely behavioral problems [b = −0.08, 95%-CI = (−0.14; −0.01), p =<sans-serif> 0</sans-serif>.027]. Presence of short-time work and decrease in income since beginning of the pandemic were used as control variables. This means that since the pandemic mothers with insecure attachment representation have an increased risk of having only a few coping mechanisms available, leading to harmful parental behaviors and ultimately affecting the mental health of their children. In conclusion, the pandemic could potentially have a particularly negative influence on mothers with an insecure attachment type and therefore on their children. Therefore, tailored interventions for families should be offered that both focus on the different types of mental health problems in children and support parents in their coping skills.